Regional variation of academic spinoffs formation - Conceicao, Oscarina (2020)
ABSTRACT: Using a self-collected longitudinal dataset that comprehends the population of academic spinoffs created in Portugal from 1995 until 2007 we investigate to what extent these firms are geographically clustered and the determinants of their geographical distribution at the time of their formation. We focus on university and agglomeration economies-related mechanisms at the municipality level. Our results show that overall academic spinoffs do not exhibit a tendency to cluster, nevertheless some local clusters do exist. Additionally, our findings show that the presence of university incubators and/or university research parks is the most relevant university-related mechanism, whereas regarding agglomeration economies all seem to be important to explain academic spinoffs distribution across municipalities.